Patients' perspective in the context of proton beam therapy: summary of a Nordic workshop. (2nd October 2020) - Ohlsson-Nevo, Emma; Furberg, Maria; Giørtz, Mette; Johansson, Birgitta; Kristensen, Ingrid; Kunni, Kristin; Langegård, Ulrica; Lysemose Poulsen, Rikke; Striem, Jörgen; Tømmerås, Veronika; Wilhøft Kristensen, Anne; Winther, Dorte; et al.
Abstract: Introduction: On 15–16 November 2019, the Skandion Clinic in Sweden hosted the first Nordic workshop on 'Patients' perspective in proton beam therapy'. The workshop was conducted to describe and compare the patient care in PBT clinics in the Nordic countries and to initiate a collaboration, with the target to ensure patient participation and reduce the risk of inequity of access by lowering the barriers for accepting PBT in a distant clinic. The overarching aim of this workshop was to describe and compare the use of patients' perspectives in the Nordic PBT clinics. Material and Methods: Twelve participants attended the workshop, representing Denmark, Norway and Sweden. The participants were registered nurses working in patient care, researchers, physicist and leaders of the Skandion Clinic. Results: The consensus of the workshop was that systematic use of patient experiences on individual and group level is essential for developing clinical practice and understanding the overall effects of PBT. A difference in how the Nordic countries use patient experiences in clinical practise was found. The importance of lowering the barriers for participation in national proton trials and proton treatment were emphasized, however, there is a lack of knowledge about individual and organizational barriers to accepting PBT, and further research is therefore needed. Conclusion: Collaboration between the Nordic countries regarding patients' perspectives in the context of PBT is of importance to compare national differences as well as to find similarities, but most importantly to learn from each other and to improve patient care. Nordic collaboration with focus on systematic collection of patient-reported outcomes in the context of PBT is unique. Collaboration in research offers the possibility to increase the inclusion of patients' perspectives in study protocols.